Research and Design of RU Type and YU Type Pulley Cutter Tooth Profile of Engine Timing System - Jianhua Guo; Zhenzhen Hu; Yizhen Wu; Junpeng Hou; Hongyuan Jiang (Jixie chuandong)
In view of the problem of the GB/T 10414-2017 Synchronous belt drive car synchronous belt pulley standard does not provide the RU type and YU type pulley standard tool tooth profile parameter, the conjugate harmonic relationship between the pulley and tool tooth profile are studied. Firstly, the conjugate tool tooth surface of the pulley tooth profile is enveloped based on the meshing principle, and the discrete data of the envelope curve is mathematically fitted to determine the mathematical model of the cutter tooth profile. Secondly, through the second enveloping process of the cutter on the pulley, it is found that there is an undercut at the top of the tooth profile of the processed pulley tooth profile. Through the study of the mechanism of undercutting, the reason of singularity of cutter surface is revealed, and tooth profile model to eliminate the singular point of cutter tooth profile curve is proposed. The tooth profile error based on pulley is within the standard tolerance range, the cutter parameter is redesigned.